Authenticity and Diversity: Enhancing Australian Hepatitis C Prevention Messages - Winter, R.; Fraser, Suzanne; Booker, N.; Treloar, C. (Federal Legal Publications, Inc, 2013)
Despite two decades of prevention activities and education, rates of hepatitis C infection remain high among people who inject drugs. In this article we draw on the findings of an extensive review of the content of print hepatitis C prevention materials circulating in Australia, examining these data in light of Petraglia’s (2009) theory of “authenticity” in social marketing. We identify three main areas in which resources could be redesigned: closer attention to language and terminology, a critical engagement with common concepts of the individual, and more acknowledgement of the role of social and structural factors in shaping injecting practice. To achieve a stronger sense of authenticity, and in turn become more equitable and efficient, future resources could address these issues using insights from social marketing literature.